Universities are committed to supporting CBBP to synergize learning, research, and community services - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A community-Based Breeding program is an alternative genetic improvement approach under smallholder livestock keeper management conditions. It was initiated in 2009 by engaging multiple of stakeholders mainly farmers, extension, research centers, ILRI, ICARDA, and Boku with little participation from universities. We understand universities have a role to support CBBP, attributed to their broader distribution in regions and Agroecology in Ethiopia, which will create a conducive environment to scale up CBBP and reach out to more smallholder farmers and pastoralists. Hence, demand was created among universities to initiate CBBP on the premise that CBBP could play a role in synergizing research, community engagement, and learning. CBBP, under the support of universities, was initiated in 2021, and more than 31 universities signed MoU and, 31 universities amended CBBP in a curriculum and supported 58 CBBP villages to synergize triple mandates of HLI. In 2023, 1 undergraduate, 3 M.Sc programs, and 1 PhD program integrated CBBP into the curriculum. In 2023, 17 CBBPs were supported by 7 Universities by allocating 9 453 591 Birr (170 335 USD) for five years, which requires channeling the money as per the agreed plan and every year. The number of students benefiting from the revamped curriculum would be 1240 and 430 in UG and PG programs, respectively, with 1670 students benefiting from the revamped curriculum. In the CBBP program, more than 5800 households benefit from University-ICARDA engagement. In the effort to strengthen CBBP, ICARDA and its partners (Universities, Research centers, and extension) are engaged in several activities, which include creating new CBBP programs, strengthening the existing CBBP, running a gap-filling capacity building, providing inputs used taking baselines for new programs (e.g., Ear tags, Burdizzo, Ear tag markers, Balances, applicators), field visits, and technical backing. ICARDA has developed a scaling framework to expand CBBP from pilot to large scale. The scaling framework is intended to transform the CBBP intervention from the community to the breed level and reach out to more farmers, in which universities play a key role. CBBP is a field learning lab, where students can learn and provide community services to the community through effective collaboration and partnership of stakeholders with a clear role and subsequent monitoring and collaboration. Community-based breeding programs require long-term investment and continuous follow-up to benefit from the innovation.